2009
DOI: 10.1017/s0007114509992728
|View full text |Cite
|
Sign up to set email alerts
|

Changing the zinc:iron ratio in a cereal-based nutritional supplement has no effect on percent absorption of iron and zinc in Sri Lankan children

Abstract: The Thriposha programme is a community-level nutrition intervention in Sri Lanka that provides a combination of energy, protein and micronutrients as a 'ready-to-eat' cereal-based food. We measured the bioavailability of Fe and Zn from Thriposha formula at two different molar ratios of Zn:Fe in order to determine the effect on Fe and Zn absorption. Children 4-7 years (n 53) were given a meal prepared with 50 g Thriposha containing 1·5 mg Zn as zinc sulphate and either 9 mg (high Fe concentration (HiFe)) or 4·5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We observed that the mean consumption of iodine-containing nutrient supplements was not satisfactory (mean = 10.77 μg/day). In addition, the iodine level of nutrient supplements, including Soy flour and Thriposha, was approximately between 0.2–0.4 μg/g [ 70 ]. Gordon et al (1998) claimed that iodine supplementation (150 μg iodine/day for 28 weeks) increased the UIC in children who had mild ID (63 μg/L) [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the mean consumption of iodine-containing nutrient supplements was not satisfactory (mean = 10.77 μg/day). In addition, the iodine level of nutrient supplements, including Soy flour and Thriposha, was approximately between 0.2–0.4 μg/g [ 70 ]. Gordon et al (1998) claimed that iodine supplementation (150 μg iodine/day for 28 weeks) increased the UIC in children who had mild ID (63 μg/L) [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haschke et al (1986) 56 No significant difference in absorption between fortified (iron, 10.2 mg/L) and unfortified product (iron, 2.5 mg/L) Szymlek-Gay et al (2016) 103 Neither supplemental iron (iron, 1. 128 No significant difference in zinc absorption between high (iron, 9 mg) and low (iron, 4.5 mg) supplementation. Phytate/phytase intake 0-3 years (n ¼ 3) Brni c et al (2017) 90 Adding 20.5 phytase units in meals (phytic acid content, 108.2 mg) can increase zinc absorption in young children.…”
Section: Reference Conclusionmentioning
confidence: 96%
“…Factors affecting zinc bioavailability. A total of 30 studies reported data on the efficacy of zinc absorption in children aged 0 to 9 years, 39,53,56,63,65,66,68,80,88,[90][91][92][94][95][96][97][98][99][100][103][104][105][123][124][125][126][127][128][129][130] of which 19 were conducted in the target age range of 0 to 3 years. 39,53,56,66,88,[90][91][92][94][95][96][97]99,100,[103][104][105]124,129 Results from these studies are summarized in Table 3.…”
Section: Data Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies have reported on zinc-iron interactions in fortified water (10), wheat flour (7,11), and other cereals (12). The effect of zinc on iron bioavailability from fortified foods, liquids, and supplements has been reviewed (13).…”
Section: Introductionmentioning
confidence: 99%